Investigation of the dielectric characteristics of materials manufactured using additive technologies - S. V. Kharalgin; M. I. Voytovich (Российский технологический журнал, 2021)
Based on the existing methods of measuring the dielectric characteristics of materials, the most optimal method for performing calculations in the electrodynamic computer-aided design system is selected by the finite integration method. Based on the calculated values of the scattering matrix, the permittivity and the tangent of the dielectric loss angle of the printed polymer samples are calculated according to a given algorithm. When evaluating the accuracy of the calculation of the dielectric characteristics, validation was performed for a sample with the specified characteristics. For a sample printed using the technology of fused filament fabrication, the influence of the filling parameters on the dielectric characteristics of the printed model in the X-band of wavelengths was estimated. The description of the model implemented in the computer-aided design system is given. By processing the simulation results, approximating dependences for the permittivity and losses on the degree of filling with the dielectric are obtained. It follows from the calculated angular diagrams that the decrease in the degree of filling of the dielectric directly affects the degree of anisotropy of the polymer obtained during printing in the plane of the extruded layers. This also increases the depth of the extremes observed at angles of 0°, 90° and 180°. The presence of these extremes is directly related to the fact that the force lines of the main wave type in the waveguide are located perpendicular to the wide wall and in a situation where the volumes of air gaps between the cylinders are parallel to the force lines of tension, there is a general decrease in the dielectric constant. For a printed sample consisting of two layers of crossed cylinders, the air volumes are parallel to the lines of force with a period of ninety degrees, which is confirmed by the results obtained. An increase in the depth of the extremes with a decrease in the degree of filling is associated with a corresponding increase in the air space between the cylinders in the layer of the printed polymer.